Thermal stratification in a cylindrical tank due to heat losses while in standby mode. (June 2019) - Bai, Yakai; Yang, Ming; Wang, Zhifeng; Li, Xiaoxia; Chen, Longfei
Highlight: Experimental and numerical study of a tank in stand by mode is performed. The Nusselt number at the side wall and top wall are fitted. A new one dimensional model for the cooling process is established and validated. Higher H/D ratio results in higher stratification when it is smaller than 3. Abstract: The liquid in an energy storage tank will become thermally stratified during cooling of the tank when the tank is not charging or discharging. This process is studied here experimentally and numerically. A two-dimensional model validated against experimental data is used to study the thermal stratification mechanisms during cooling. The results show that natural convection mainly along the upper side of the cylindrical tank creates a boundary layer along the sidewall that drives cooled water down the side. The two-dimensional analysis is used to create a one-dimensional model for the cooling process that is validated against the experimental data. The one-dimensional model is then used to investigate the influence of the height to diameter aspect ratio on the cooling process. A tank with an aspect ratio of 1:1 has the highest energy efficiency, highest exergy efficiency, and lowest entropy generation during cooling. Further study shows that when the aspect ratio is smaller than 3, the thermal stratification increases greatly with increasing aspect ratio. Aspect ratios bigger than 3 have little influence on the thermal stratification.